1998
DOI: 10.7326/0003-4819-129-7-199810010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Family Responsibilities and Gender to the Productivity and Career Satisfaction of Medical Faculty

Abstract: Compared with female faculty without children and compared with men, female faculty with children face major obstacles in academic careers. Some of these obstacles can be easily modified (for example, by eliminating after-hours meetings and creating part-time career tracks). Medical schools should address these obstacles and provide support for faculty with children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
307
3
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(332 citation statements)
references
References 17 publications
8
307
3
14
Order By: Relevance
“…6,7 According to the Association of American Medical Colleges (AAMC), in 2007-2008, women accounted for 34% of all medical faculty and 17% of full professors. Although women have comprised >30% of medical students for nearly three decades 8 and much has been written on the disproportionate lack of advancement of women physicians into senior and leadership positions, [9][10][11][12] the AAMC data indicate that women are achieving leadership positions in the top echelons of academic medicine in unprecedented numbers. Of all departments in academic medical centers (AMCs) 12% are now led by women (vs. 6% in 1998) and only 6 of 126 AMCs remain with no women chairs.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 According to the Association of American Medical Colleges (AAMC), in 2007-2008, women accounted for 34% of all medical faculty and 17% of full professors. Although women have comprised >30% of medical students for nearly three decades 8 and much has been written on the disproportionate lack of advancement of women physicians into senior and leadership positions, [9][10][11][12] the AAMC data indicate that women are achieving leadership positions in the top echelons of academic medicine in unprecedented numbers. Of all departments in academic medical centers (AMCs) 12% are now led by women (vs. 6% in 1998) and only 6 of 126 AMCs remain with no women chairs.…”
Section: Introductionmentioning
confidence: 99%
“…While this may be hard to explain, this phenomenon may suggest attitudinal issues as a strong determinant for success. This is because women in employment tend to perform in one aspect to the detriment of the other (Carr, Ash, Friedman, Scaramucci, Barnett, Szalacha, Palepu, Moskowitz, 1998). Studies have however affirmed a strong relationship between work preferences and attitudes (Hakim, 2001); however, studies have equally added that attitudes towards work are a combination of many factors ranging from educational attainment, their ethnic and social background, their employment record and age all play important roles in attitudes (Kangas and Rostgaard, 2007).…”
Section: Another Respondentmentioning
confidence: 98%
“…Female physicians may be more influenced by nonmedical factors such as child care responsibilities, and these responsibilities may limit their desire or ability to take on more work, particularly if it is time-consuming. 25 Alternatively, men and women physicians may have different ideas about procedures in general. Other studies have found that female graduates of family medicine training programs do fewer complex procedures in their practice than do male graduates.…”
Section: Discussionmentioning
confidence: 99%